2020
DOI: 10.3390/ijms21249390
|View full text |Cite
|
Sign up to set email alerts
|

Transferrin-Bound Doxorubicin Enhances Apoptosis and DNA Damage through the Generation of Pro-Inflammatory Responses in Human Leukemia Cells

Abstract: Doxorubicin (DOX) is an effective antineoplastic drug against many solid tumors and hematological malignancies. However, the clinical use of DOX is limited, because of its unspecific mode of action. Since leukemia cells overexpress transferrin (Tf) receptors on their surface, we proposed doxorubicin–transferrin (DOX–Tf) conjugate as a new vehicle to increase drug concentration directly in cancer cells. The data obtained after experiments performed on K562 and CCRF-CEM human leukemia cell lines clearly indicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…Long-term cytotoxicity study showed ( Figure 2 c) that after treatment with FA 2 -dPEG-DOX 2 at 100 μM concentration (regarding DOX), viability values of the treated MDA-MB-231 cells were similar to the untreated control until 48 h. However, treatment with FA 2 -dPEG-DOX 2 reduced cell viability significantly after 48 h (compared to the control) and sustained at an approximately constant level for 168 h. The results show slow DOX release in the cell culture medium investigated. Similar studies often do not investigate simulated drug release profiles because they may not be predictive for in vivo conditions [ 15 , 16 , 17 , 18 , 19 , 20 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Long-term cytotoxicity study showed ( Figure 2 c) that after treatment with FA 2 -dPEG-DOX 2 at 100 μM concentration (regarding DOX), viability values of the treated MDA-MB-231 cells were similar to the untreated control until 48 h. However, treatment with FA 2 -dPEG-DOX 2 reduced cell viability significantly after 48 h (compared to the control) and sustained at an approximately constant level for 168 h. The results show slow DOX release in the cell culture medium investigated. Similar studies often do not investigate simulated drug release profiles because they may not be predictive for in vivo conditions [ 15 , 16 , 17 , 18 , 19 , 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…PDCs. Research carried out with various polymers, including PEG, showed promise due to increased water solubility and circulation time in the body, and multivalent attachment to receptors FR [ 15 , 16 , 17 , 18 , 19 , 20 ]. Despite the progress achieved in the field, several obstacles currently impede the clinical translation of PDC-based therapeutics [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Also, long circulating properties of nanosystems were observed, as discussed by Wang et al 45 As reported by Jedrzejczyk et al, a Tf-containing conjugate can be used as a vehicle to increase drug concentration in leukemia cells overexpressing Tf receptors on their surface, which is also in accordance with the tumor accumulation observed in this study. 46 The dramatic increase accumulation in drug-loaded nanosystems in tumor tissue compared with free-drug solutions can be explained by the theory that solid tumors have leaky microvasculature and nanosized particles being able to passively target tumors owing to the enhanced permeability-and-retention effect. 47 Li et al also argued that less drug distribution in kidneys can decrease side effects and lead to better antitumor efficiency, which was achieved by the nanosystems in the present research.…”
Section: Discussionmentioning
confidence: 99%
“…There is limited data on differences in sensitivity between normal human peripheral blood leukocytes and leukemia cells to DOX. Jedrzejczyk et al [34] compared the cytotoxic effects of DOX in human peripheral blood mononuclear cells (PBMCs) and the K562 leukemia cell line by analyzing the mitochondrial activity of respiratory chain oxidoreductases. It was shown that the IC50 concentration of DOX in the K562 leukemia cell line is significantly lower compared to PBMCs [34].…”
Section: Methodsmentioning
confidence: 99%